2021
DOI: 10.21125/edulearn.2021.2274
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Institutions - The Synergies Between Total Quality Management and Social Responsibility

Abstract: Total Quality Management (TQM) is an integrated management effort aimed at improving quality at any level to achieve excellence and corporate social responsibility, like most management concepts, has been gradually incorporated into the management practice of organizations. It is important that in order to effectively manage socially responsible business, the organization needs to define strategies, programmes and action plans. CSR and TQM can improve the institution efficiency, reduce bureaucracy by eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Third, with a path coefficient of 0.0.989 and a qualitative correlation coefficient of 0.390094, the influence of TQM on the quality of community service was assessed to be significant at 0.01. These findings are consistent with those of previous studies ( Nogueiro et al, 2011 , 2017 , 2022 ; Khoja et al, 2017 ; Banerjea, 2018 ; Yeung, 2018 ; Castillo, 2020 ), while these results differ from Koch (2003) which confirmed that the effect is small and identified the reasons for this.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Third, with a path coefficient of 0.0.989 and a qualitative correlation coefficient of 0.390094, the influence of TQM on the quality of community service was assessed to be significant at 0.01. These findings are consistent with those of previous studies ( Nogueiro et al, 2011 , 2017 , 2022 ; Khoja et al, 2017 ; Banerjea, 2018 ; Yeung, 2018 ; Castillo, 2020 ), while these results differ from Koch (2003) which confirmed that the effect is small and identified the reasons for this.…”
Section: Discussionsupporting
confidence: 93%
“… Castillo (2020) reaffirmed the necessity to develop and implement TQM concepts to all aspects of higher education academic units, including teaching, research, community services, and administrative support. Furthermore, Nogueira emphasized in his different studies that TQM and CSR are two increasingly significant dimensions in creating a sustainable and hopeful future for all stakeholders, and that they are important dimensions in achieving a sustainable and promising future for all stakeholders (among others, students and workers employers, and society in general; Nogueiro et al, 2011 , 2017 , 2022 ). In Algerian universities, Khelifa et al (2013) and Keffane et al (2020) emphasized the existence of numerous effects of total quality management, including improving the quality of community service.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CSR in education focuses on the institution's ethical, legal, and philanthropic responsibilities towards its stakeholders. The intersection of TQM and CSR, particularly in higher education, offers a unique perspective on institutional governance, emphasizing both operational effectiveness and societal impact (9) . In the context of higher education, particularly in the UAE, Almuntfjy and Kowang (10) analyze the impact of TQM and CSR on financial performance.…”
Section: Introductionmentioning
confidence: 99%